Assessment of knowledge of midwives about the scope of professional responsibility under the amended provisions of law - Belowska, Jarosława; Dykowska, Grażyna; Sienkiewicz, Zofia; Gotlib, Joanna (Polish Journal of Public Health, 2014)
Introduction. To work safely, knowledge of law is crucial for midwives who should be familiar with the midwife’s rights and duties as well as their professional responsibility. Aim. Assessment of knowledge of midwives about their professional responsibility. Material and methods. A total of 103 MA Midwifery students of the Medical University of Warsaw, including 55 working and 48 not working as midwives. A diagnostic poll, original anonymous questionnaire, 25 close-ended questions, 8 openended questions. Statistical analysis: STATISTICA 10.0, Mann-Whitney U test, p<0.05. Results. Seventy-one percent of the study participants had knowledge of the binding provisions of law and 83% considered this kind of knowledge as necessary in their professional activity. Twenty-four percent of the total did not know any legal regulations. Thirty percent was not familiar with the Nurses and Midwives Act. Only 52% of the study participants were knowledgeable about the legal protection of midwives and indicated the protection established for public officers. Forty-six percent of the total said that the Act on Professional Self-Government of Nurses and Midwives of July 1st, 2011 regulates the issue of self-governance. As many as 30 study participants knew that membership in the self-governing body of midwives is obligatory. Conclusions. Knowledge of nurses about professional responsibility under amended provisions of law is insufficient and does not improve with experience as a midwife. Due to the fact that new acts on professional responsibility of midwives were implemented in Poland beginning in January 1st, 2012, it is advisable to extend qualifications and knowledge of midwives in order to improve their knowledge of professional issues. Midwives should constantly update their knowledge of legal regulations on their profession.